An overview of the phenotypic and genotypic characteristics of multidrug-resistant Mycobacterium tuberculosis isolates from four Asian countries - Ang, C. F.; Ong, Chia Sui; Rukmana, A.; Pham Thi, K. L.; Yap, Sook Fan; Ngeow, Yun Fong; Ho, M. L.; Sudiro, T. M.; Bela, B.; Jordaan, A. M.; Streicher, E. M.; Victor, T. C. (Microbiology Society, 2008)
An overview of the phenotypic and genotypic characteristics of multidrug-resistant Mycobacterium tuberculosis isolates from four Asian countries